Direksi Wanita, Biaya Lingkungan dan Tata Kelola Iklim terhadap Pengungkapan Emisi Karbon: Moderasi Kepemilikan Institusional - Puteri, Alyafira Salsabila; Baroroh, Niswah (ARBITRASE: Journal of Economics and Accounting, 2026)
This study aims to analyze the effect of female directors, environmental costs, and climate governance on carbon emissions disclosure, as well as to examine the moderating role of institutional ownership. The novelty of this study lies in the empirical testing of the effectiveness of institutional ownership as an external monitoring mechanism in strengthening the relationship between board characteristics, environmental cost commitments, and climate governance on carbon emissions disclosure in high-emission energy companies in Indonesia. This study uses a quantitative approach with secondary data from energy sector companies listed on the IDX for the period 2022–2024, analyzed using multiple linear regression with a moderation approach. The results show that female directors have a coefficient of 0.0869 with a significance value of 0.2880, thus having no significant effect on carbon emissions disclosure. Conversely, environmental costs have a positive and significant effect with a coefficient of 0.0330 and a significance of 0.0000, while climate governance has a positive and significant effect with a coefficient of 0.4460 and a significance of 0.0000. In addition, institutional ownership was not proven to moderate the relationship between independent variables and carbon emissions disclosure, as indicated by all moderation significance values being greater than 0.05. This study makes a theoretical contribution by showing that legitimacy theory is supported by the influence of environmental costs on carbon emissions disclosure, agency theory is supported in the direct relationship between climate governance but not in the role of institutional ownership as a moderating variable, while top-level theory does not obtain empirical support from the influence of female directors. This study provides empirical contributions by expanding the evidence on the role of internal corporate mechanisms and institutional ownership in carbon emissions disclosure practices, particularly among energy sector companies in Indonesia. Conceptually, the results of this study confirm that carbon emissions disclosure is more influenced by internal corporate commitments and policies. Further research is recommended to expand the scope of sectors, extend the observation period, and develop indicators that better reflect the quality of climate governance implementation and carbon emissions disclosure.